2022
DOI: 10.1002/advs.202203008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong Hybrid Fibers with Tunable Macromolecular Interfaces of Graphene Oxide and Carbon Nanotube for Multifunctional Applications

Abstract: Individual carbon nanotubes (CNT) and graphene have unique mechanical and electrical properties; however, the properties of their macroscopic assemblies have not met expectations because of limited physical dimensions, the limited degree of dispersion of the components, and various structural defects. Here, a state‐of‐the‐art assembly for a novel type of hybrid fiber possessing the properties required for a wide variety of multifunctional applications is presented. A simple and effective multidimensional nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…The resulting graphite-like layers led to an increase in the void thickness owing to folding, splitting, or tilting [47]. This deteriorated the tensile strength of the fibers, as reported in a previous study [48,49]. It is confirmed that the tensile strengths of the fibers heat-treated at 2,700 • C are lower than those of the fibers heat-treated at 1,400 • C at the same PI content (Fig.…”
Section: Microstructures Of Carbonized and Graphitized Fiberssupporting
confidence: 84%
“…The resulting graphite-like layers led to an increase in the void thickness owing to folding, splitting, or tilting [47]. This deteriorated the tensile strength of the fibers, as reported in a previous study [48,49]. It is confirmed that the tensile strengths of the fibers heat-treated at 2,700 • C are lower than those of the fibers heat-treated at 1,400 • C at the same PI content (Fig.…”
Section: Microstructures Of Carbonized and Graphitized Fiberssupporting
confidence: 84%
“…However, for the Warburg impedance, the high knee frequency is desirable for materials in favour of power generation. 38,39 It should be noted that there may be a trade-off between electrical conductivity and electrochemical performance. Therefore, the structural and electrochemical properties of the Ml-GO/CNT interface can be specically tailored by adjusting the interfacial ratio of GO to CNT NFMs.…”
Section: Resultsmentioning
confidence: 99%
“…On SS-CNTFs with LD ~ 0.19 tex with heating to 1700°C, they achieved high tenacity (3.84 N tex −1 ) and thermal conductivities (482 W m −1 K −1 ), although the ductility and work of rupture are partially sacrificed. The last article used the CNT and graphene oxide hybrid liquid crystal solution to produce hybrid fibers ( 40 ). They believe that the flexible graphene oxides intercalate between nanotubes, which maximizes the contact between elements.…”
Section: Resultsmentioning
confidence: 99%